2006
DOI: 10.1051/0004-6361:20065501
|View full text |Cite
|
Sign up to set email alerts
|

Superclusters of galaxies from the 2dF redshift survey

Abstract: Aims. We investigate properties of superclusters of galaxies found in of the 2dF Galaxy Redshift Survey, and compare them with properties of superclusters from the Millennium Simulation. Methods. We study the dependence of various characteristics of superclusters on their distance from the observer, on their total luminosity, and on their multiplicity. The multiplicity is defined by the number of Density Field (DF) clusters in superclusters. Using the multiplicity we divide superclusters into four richness cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 48 publications
4
47
0
Order By: Relevance
“…The mean and maximum number densities of galaxies in rich superclusters are higher than in poor superclusters. Rich superclusters are more asymmetrical than poor superclusters (Einasto et al 2007a). Rich superclusters contain high-density cores (Einasto et al 2007c).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean and maximum number densities of galaxies in rich superclusters are higher than in poor superclusters. Rich superclusters are more asymmetrical than poor superclusters (Einasto et al 2007a). Rich superclusters contain high-density cores (Einasto et al 2007c).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The overall morphology of superclusters has been studied by several authors (Kolokotronis et al 2002;Basilakos 2003;Costa-Duarte et al 2011), we refer to Einasto et al (2007a) for a review of the properties of superclusters. The shapes and sizes of superclusters can be used to compare the observed superclusters with those obtained from cosmological simulations (Kolokotronis et al 2002;Einasto et al 2007a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…intermediate redshifts. Deeper spectroscopic surveys will certainly change that, as can be extrapolated from Einasto et al (2007a) who identified 543 superclusters with z < 0.2.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that in richer superclusters groups and clusters of galaxies are also richer, and they contain a larger fraction of red, non-star forming galaxies than poor superclusters (Einasto et al 2007(Einasto et al , 2007a.…”
Section: Introductionmentioning
confidence: 99%